2016
DOI: 10.1089/tmj.2016.0050
|View full text |Cite
|
Sign up to set email alerts
|

Access to Specialized Care Through Telemedicine in Limited-Resource Country: Initial 1,065 Teleconsultations in Albania

Abstract: The Integrated Telemedicine and e-Health program of Albania has become a useful tool to improve access to high-quality healthcare, particularly in high demanding specialty disciplines. A number of challenges were identified and these should serve as lessons for other countries in their quest to establish nationwide telemedicine programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
1
23
0
2
Order By: Relevance
“…The kind of clinical disciplines that can be added to the program depends on many factors, but these are mostly dictated by the clinical needs of regional hospitals and physician leaders. 19 No significant difference in the need for the system was observed among the treatment divisions. This means that a robot can be widely used in all treatment divisions.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The kind of clinical disciplines that can be added to the program depends on many factors, but these are mostly dictated by the clinical needs of regional hospitals and physician leaders. 19 No significant difference in the need for the system was observed among the treatment divisions. This means that a robot can be widely used in all treatment divisions.…”
Section: Discussionmentioning
confidence: 91%
“…It was also reported that live teleconsultations need to be in the proximity of physicians, nurses, and patients or go completely mobile, such as through secured tablets and iPods. 19 Response time is an important factor for facilitating rapid identification and intervention for diseases, especially for emergency consultations. 3 In the management of crises or emergencies, even personal digital assistants can be used for data transfer and video calls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hopefully, these examples, new U.S. and other government's support, along with other lessons from around the world that have been well documented [29][30][31][32] will ensure continuation, expansion, and sustainability of current enthusiasm for telemedicine across the world, and in all clinical disciplines.…”
Section: Covid-19 and The Rise Of Telemedicinementioning
confidence: 99%
“…Telehealth is defined as the use of telecommunications to provide health information and care across distance [ 1 ]. It may improve access to specialists by redistributing expertise in given care contexts virtually [ 2 ]. The adoption of telehealth technologies greatly reduces location as a barrier to accessing high-quality treatment and care, opening up new opportunities for healthcare providers to engage with patients and other professionals across distances.…”
Section: Introductionmentioning
confidence: 99%